Guided Multispectral Optoacoustic Tomography for 3D Imaging of the Murine Colon - Knieling, Ferdinand; Brown, Emma L.; Eckstein, Markus; Thoma, Oana-Maria; Wachter, Felix; Mandelbaum, Henriette; Ludwig, Petra; Claßen, Merle; Oraiopoulou, Mariam Eleni; Rother, Ulrich; Neurath, Markus; Wölfle, Joachim; et al. (Advanced Science, 2025)
Multispectral optoacoustic tomography is a promising medical imaging modality that combines light and sound to provide molecular imaging information at depths of several centimeters, based on the optical absorption of endogenous chromophores, such as hemoglobin. Assessment of inflammatory bowel disease has emerged as a promising clinical application of optoacoustic tomography. In this context, preclinical studies in animal models are essential to identify novel disease-specific imaging biomarkers and understand findings from emerging clinical pilot studies, however to-date, these studies have been limited by the precise identification of the bowel wall. Herein, a transrectal-absorber guide is applied, serving as a high-contrast landmark for 3D optoacoustic tomography of the colon. This study shows that guided multispectral optoacoustic tomography is able to measure changes in blood oxygenation status over the course of acute, chemically-induced colitis in mice and correlates with standard disease activity scores. This novel approach depicts intestinal hemoglobin composition non-invasively during murine inflammation. These results underscore the potential for optoacoustic imaging in translational inflammatory bowel disease research.
CRIS-Team Scopus Importer:2025-01-31
Keywords: dextran sodium sulfate induced colitis; inflammatory bowel disease; multispectral optoacoustic tomography; murine acute colitis; optoacoustic imaging; photoacoustic imaging